Development of Application Program Model Couseling to Improve Teacher Counseling Performance at Junior High School in Takalar - Kurniati, Kurniati (Universitas Negeri Makassar, 2017)
Abstrack : The aims of research are : (1) to describe saving BK information service at SMP In Takalar, (2) to produce program aplication model of guindance counseling, This research is developing research. Subjects of research are di SMP Negeri 1 POLUT, SMP Negeri 2 POLUT, SMP Negeri 3 POLUT, SMP Negeri 4 POLUT, SMP Negeri 5 POLUT, SMP Negeri 1 Takalar, SMP Negeri 2 Takalar dan SMP Negeri 3 Marbo. To collecting the data used scoring scale system of BK program aplication and it was anlyzed quantitative descriptive. Result of reseacrh shown that (1) describe saving BK information service at SMP In Takalar, (2) to produce program aplication model of guindance counseling and this product which has been developed based on BK teacher’s needs in school,